Subsea Pipeline Corrosion: A Review of Detection Methods, Mechanisms and Prevention Strategies - Muammar Kadhafi (Collaborate Engineering Daily Book Series, 2023)
Subsea pipelines are one of the important components in the oil and gas industry, which function to transport fluids from wells to surface facilities. However, subsea pipelines are susceptible to corrosion due to interaction with the aggressive marine environment, which can cause structural damage, leaks, and even failure of the pipeline. Therefore, effective and efficient underwater pipe corrosion detection methods, mechanisms, and prevention strategies are needed. This article aims to provide an overview of various detection methods, mechanisms, and prevention strategies for undersea pipeline corrosion that have been developed by researchers. Subsea pipeline corrosion detection methods can be divided into two categories, namely internal methods and external methods. Internal methods involve measuring physical parameters inside the pipe, such as pressure, flow, temperature, and fluid composition. External methods involve the use of non-destructive inspection technologies, such as ultrasonic, radiographic, electromagnetic, and acoustic.